Pathological Chemotherapy Response Score in Patients Affected by High Grade Serous Ovarian Carcinoma: The Prognostic Role of Omental and Ovarian Residual Disease - Santoro, Angela; Angelico, Giuseppe; Piermattei, Alessia; Inzani, Frediano; Valente, Michele; Arciuolo, Damiano; Spadola, Saveria; Mulè, Antonino; Zorzato, Piercarlo; Fagotti, Anna; Scambia, Giovanni; Zannoni, Gian Franco (Frontiers in Oncology, 2019)
Background: The chemotherapy response score (CRS) has emerged as a simple and reproducible histopathological grading system for assessing chemotherapy response in patients affected by ovarian high-grade serous carcinoma. Objective: To evaluate the prognostic impact of histological tumor response in ovarian and omental surgical specimens from patients with advanced stage ovarian high-grade serous carcinoma. Study Design: A cohort of 161 women were identified from the database of Department of Gynecology, ‘Fondazione Policlinico Universitario Agostino Gemelli IRCCS’ of Rome, Italy between January 2014 and December 2017 with a follow-up of 65 months. All the omentum, the ovarian tissue and peritoneal samples, defined as “other sites”, were reviewed by gynaecological pathologists to assign a CRS of 1 to 3 to the omentum and ovarian sites and a score of 0 to 1 to the peritoneal tissue. The Cox proportional hazards regression and the log-rank test were used to assess the survival pattern and the prognostic value of the CRS adjusting for age and stage. The Kaplan-Meier method was applied to estimate the progression free and overall survival. Results: The evaluation of adnexal disease showed significant differences in PFS, both in univariate and in multivariate analyses. On PFS univariate analysis, ovCRS1 vs ovCRS3: HR, 2.27; 95% CI, 1.37-3.77; p=0.001; ovCRS2 vs ovCRS3: HR, 1.83; 95% CI, 1.03-3.23; p=0.04 and on PFS multivariate model ovCRS1 vs ovCRS3; HR, 2.53; 95% CI, 1.5-4.24; p=0.001 and ovCRS2 vs ovCRS3; HR, 1.90; 95% CI, 1.08-3.37; p=0.03. Regarding the omental residual disease, as expected, CRS showed a significant prognostic value for OS and PFS; in detail the median PFS of patients with CRS1, 2 and 3 was 15, 15 and 22 months, respectively, the median OS was 41 and >50 months, respectively. Moreover, the univariate analysis for OS suggested that in our cohort the “other sites” score of 0 was significantly associated with an improvement in overall survival compared to score 1. Conclusions: We demonstrated for the first time the prognostic significance of adnexal CRS confirming also the prognostic role of omental CRS.